Immobilization of heavy metals (Cd, Zn, and Pb) in different contaminated soils with swine manure biochar. Issue 1 (1st January 2021) - Yang, Fang; Wang, Bing; Shi, Zeming; Li, Ling; Li, Yang; Mao, Zhiqiang; Liao, Luyun; Zhang, Heng; Wu, Yang
ABSTRACT: To explore the feasibility of biochar for reducing mobility and bioavailability of heavy metals in different contaminated soils, batch incubation experiments including column leaching and pot experiments were conducted to investigate the effects of biochar input on soil pH, the bioavailability of heavy metals (Cd, Zn, and Pb) and their species in three different contaminated soils treated with different swine biochar application rates. The results show that biochar has more potential for pH improvement in acidic soils than neutral and alkaline soil. After 42 d incubation, the pH values of the acidic soils increased from 5.90 to 7.23, while the pH values of neutral/alkaline soils did not change significantly. The available heavy metals showed a decreasing trend as the biochar application rate increases. The order of the immobilization effect is Pb>Zn>Cd. Possible immobilization mechanisms are mainly ion exchange, complexation, π bond action and precipitation on the surface of biochar.